2006
DOI: 10.1007/s00221-006-0779-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neuronal activity in CNS pain pathways following propofol administration in rats: Fos and EEG analysis

Abstract: We studied Fos expression in the central nociceptive pathways at different sedative levels in order to clarify the central mechanism of propofol's nociceptive action. Sprague-Dawley rats received propofol (PRO) or pentobarbital (PEN) and were divided into two groups with different doses of drug administration (light and deep sedative levels) based on the electroencephalogram analysis. Rats at each sedative level received heat stimulation to their face and Fos immunohistochemistry was performed at various brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…It has been shown that PRO has a depressive action on neuronal activity in the whole brain areas, reflected by a decrease in EEG activity 26. We observed a similar EEG depression in rats that is observed in humans during PRO infusion.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…It has been shown that PRO has a depressive action on neuronal activity in the whole brain areas, reflected by a decrease in EEG activity 26. We observed a similar EEG depression in rats that is observed in humans during PRO infusion.…”
Section: Discussionsupporting
confidence: 84%
“…1A and B. Studies show that the depth of hypnosis can be evaluated in animals by i-EEG analysis in which the EEG amplitude was measured and the duration of amplitude depression was calculated 4,10,15,26,31,33,46,47. Thus, we introduced the i-EEG analysis to measure the depth of hypnosis during intravenous administration of PRO or PEN.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the same studies showed that high concentrations of propofol did not affect the expression of c-Fos, JunB, or Egr-1 in culture [10,11]. In contrast, Hamaya et al [12] reported that propofol increases the expression of c-Fos and Jun B in the rat brain; whereas Kubota and coworkers [13] showed that propofol regulates the expression of c-Fos in brain slices. Therefore, the interaction between propofol and these immediate early transcription factors is still under debate.…”
Section: Introductionmentioning
confidence: 99%